Repellency of α-pinene against the house fly, Musca domestica. (September 2015) - Haselton, Aaron T.; Acevedo, Angela; Kuruvilla, Jacob; Werner, Eric; Kiernan, Jaydon; Dhar, Preeti
Graphical abstract: The terpenes (1S)-(−)-α-pinene1 and (1R)-(+)-α-pinene2 exhibited repellent properties against house flies and both compounds elicited electrophysiological responses from in situ antennal preparations. Highlights: Repellent properties of α-pinene enantiomers against house flies has been investigated. Adult flies (both sexes) avoided α-pinene enantiomers (constant air flow conditions). House flies avoided tarsal contact with filter paper saturated withS- α-pinene. 1S, 5S and 1R, 5R pinenes are electrophysiologically active on female house fly antennal preparations. Abstract: Musca domestica L. is a non-biting nuisance fly that is capable of transmitting a large variety of pathogens to humans and non-human animals. Natural compounds and their derivatives, which are often less toxic than entirely synthetic compounds, may be used as repellents against M. domestica as part of comprehensive pest control and disease mitigation programs. This work investigates the repellent properties of the natural compound α-pinene against M. domestica . Adult house flies of both sexes avoided the volatile plant-derived terpenes (1S)-(−)-α-pinene1 and (1R)-(+)-α-pinene2 in constant air flow laboratory conditions, with1 exhibiting a stronger repellent effect. House flies also avoided tarsal contact with filter paper saturated with1 . Furthermore, both1 and2 are electrophysiologically active on in situ female house fly antennal preparations. These findings demonstrate that α-pinene exhibits natural baseline repellency against the house fly, elicits a specific physiological response in this fly, and that functional or structural modification of1 in particular may yield novel fly repellents with desirable properties.